MENUMBUHKEMBANGKAN MINAT BACA MENUJU MASYARAKAT LITERAT - Wahyuni, Sri (Diksi, 2010)
Research findings show that in general Indonesian students' reading ability is stilllow. This is attributable to, among others, poor reading habit, which is caused by lowreading motivation. Several aspects cause low reading motivation: (1) family andneighborhood environments that do not support reading habit, (2) society's low bookbuyingpower, (3) limited number of good libraries, (4) negative effects of electronic mediadevelopment, (5) learning model that in general does not make students read, and (6)inappropriate learning system for reading. To improve reading motivation several attemptscan be made: (1) making children get used to reading since their early age, (2) providinginteresting books, (3) creating an environment conducive for reading, (4) reconstructingthe library performance to make it interesting, and (5) developing a learning model forreading that is enjoyable, varied, and educative.Keywords: reading motivation, literate society